Tool wear and its effect on the surface integrity and fatigue behavior in high-speed ultrasonic peening milling of Inconel 718. (February 2023) - Yin, Xiaoming; Liu, Yihang; Zhao, Shicai; Li, Xun; Geng, Daxi; Zhang, Deyuan
Abstract: Ultrasonic-assisted technology has proven effective for Inconel 718 milling. This study compared tool life and tool wear forms and wear mechanisms at different wear states in high-speed Ultrasonic Peening Milling (UPM) and Conventional Milling (CM). The influence of different tool wear states on the surface integrity index and fatigue performance were systematically analyzed. The results showed 32.5% increase in tool life in UPM owing to lower tool wear compared to that in CM. More important, UPM was significantly more effective in improving machined surface quality and fatigue life with an average increase of 4–17 times.